2021
DOI: 10.1172/jci.insight.149229
|View full text |Cite
|
Sign up to set email alerts
|

Glia limitans superficialis oxidation and breakdown promote cortical cell death after repetitive head injury

Abstract: Repetitive head injury promotes free radical dependent degradation of the glia limitans superficialis -a crucial structural barrier that protects the brain parenchyma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…Interestingly, repetitive mTBI was found to disrupt this reparative process entirely if the initial injury did not have sufficient time to recover. A second mTBI encountered within 1 day of the first impeded angiogenesis, elevated cell death / barrier leakage, and promoted a massive recruitment of inflammatory myelomonocytic cells 50,102 . Whether the calvaria bone marrow 29,30 plays a role in the rapid recruitment of infiltrative cells after mTBI is unknown, but this seems likely given the direct vascular channels from the skull bone marrow to the meninges.…”
Section: Immune Response To Injury Infection and Neurodegenerationmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, repetitive mTBI was found to disrupt this reparative process entirely if the initial injury did not have sufficient time to recover. A second mTBI encountered within 1 day of the first impeded angiogenesis, elevated cell death / barrier leakage, and promoted a massive recruitment of inflammatory myelomonocytic cells 50,102 . Whether the calvaria bone marrow 29,30 plays a role in the rapid recruitment of infiltrative cells after mTBI is unknown, but this seems likely given the direct vascular channels from the skull bone marrow to the meninges.…”
Section: Immune Response To Injury Infection and Neurodegenerationmentioning
confidence: 99%
“…Currently, there are no approved treatments that improve outcomes after TBI, and a deeper understanding of the immune response and repair process in patients with these injuries is essential. Intravital imaging in rodents has shown that treatment with the ROS scavenger, glutathione, is an excellent therapeutic, especially when applied transcranially to the mTBI lesion 74,100,102 . It preserves integrity of the glia limitans superficialis, which in turn reduces immune cell activation / recruitment and cell death in the underlying brain parenchyma.…”
Section: Immune Response To Injury Infection and Neurodegenerationmentioning
confidence: 99%
See 3 more Smart Citations